2021
DOI: 10.1002/crat.202100005
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Dielectric and Raman Spectroscopy of La3+–Ni2+–Zn2+ Substituted M‐Type Strontium Hexaferrites

Abstract: In this work, M‐type strontium nanohexaferrites with chemical composition Ba0.8−xSr0.2LaxFe12−x−yNixZnyO19 (x = 0.00, 0.05, 0.10; y = 0.00, 0.08, 0.16) are prepared using sol–gel auto‐combustion technique. The formation of single phase hexagonal ferrites is confirmed from XRD analysis. It also reveals the presence of magnetite and the crystallites sizes are in the range of 21.31–29.91nm. The lattice constants are found to decrease with an increase in cation substitution. The FTIR spectra of the sample show thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…On the other side, the substitution of 'Cu' in the SLCHF sample results in a minor intensity of the resonance band compared to the parent compound. The difference in the ionic radii between Fe 3+ and Cu 2+ ions in B coordination causes a local distortion and vibrational bands of distorted polyhedral [39]. The broadening of the 4f 2 and 12k peaks compared to the SLHF sample indicates the presence of a disorder in the crystal sites as mentioned previously.…”
Section: Raman Spectroscopy (Rs)supporting
confidence: 62%
“…On the other side, the substitution of 'Cu' in the SLCHF sample results in a minor intensity of the resonance band compared to the parent compound. The difference in the ionic radii between Fe 3+ and Cu 2+ ions in B coordination causes a local distortion and vibrational bands of distorted polyhedral [39]. The broadening of the 4f 2 and 12k peaks compared to the SLHF sample indicates the presence of a disorder in the crystal sites as mentioned previously.…”
Section: Raman Spectroscopy (Rs)supporting
confidence: 62%
“…In addition, it can be shown that at x � 0.4, greater values of the real part and imaginary part ε″ were achieved in comparison to other samples. Koop's theory has been used to explain this kind of high dielectric constant event [28].…”
Section: Resultsmentioning
confidence: 99%